SYNTHESIS AND SPECTROSCOPIC STUDIES OF MANGANESE(II),COBALT(II), NICKEL(II), COPPER(II), ZINC(II) AND CADMIUM(II)COMPLEXES WITH SCHIFF BASE DERIVED FROM 1,2-DIPHENYL-3-METHYL-4-AMINO-5-OXO-PYRAZOLE WITH BENZALDEHYDE - Al-Amery, Mohammed (Iraqi Journal of Science, 2024)
The synthesis and characterization of new complexes of Mn(II), Co(II), Ni(II),Cu(II) ,Zn(II) and Cd(II) ions with bidentate Schiff base 1,2-diphenyl-3-methyl-4-benzaladene-5-oxo-pyrazole ligand which was prepared via the condensationreaction of both benzaldehyde with 1,2-diphenyl-3-methyl-4-amino-5-oxo-pyrazolein acidic medium. The complexes were synthesized by treating an ethanolic solutionof the ligand with appropriate amount of metal salts [1:2] [M:L] ratio. Thecomplexes were characterized by metal and elemental analysis, FTIR, electronicspectra, molar conductivity, magnetic susceptibility and mole ratio. According to theobtained data the probable coordination geometries of manganese, cobalt, nickel,copper, zinc and cadmium ions in these complexes with nitrogen and oxygen asdonor atoms are octahedral. All complexes were found to be non-electrolyte systemsin absolute ethanol, and the complexes were formulated as [ML2Cl2]n H2O.